Editorial - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
The increasing interest in learning English has had an impact on the alternatives students are offered to study the language as well as on the particularities of classroom management teachers have to be aware of nowadays. Hence, our conceptualizations about a classroom have to include different kinds of learning and teaching settings such as traditional face-to-face work; virtual-learning spaces to allow the learners to build a study path while tutors monitor and assist students when necessary; faceto- face study periods combined with alternating tutoring sessions; and mentoring sessions to support autonomous, semi-autonomous or self-instruction learning. This, in turn, opens doors to questions concerning a variety of issues that are born in the midst of the complex realities we face in such teaching and learning scenarios.